Predictive value of orthopedic evaluation and injury history at the NFL combine - Brophy, R. H.; Chehab, E. L.; Barnes, R. P.; Lyman, S.; Rodeo, S. A.; Warren, R. F. (Medicine & Science in Sports & Exercise, 2008)
Abstract: Purpose: The National Football League (NFL) holds an annual combine to evaluate college football athletes likely to be drafted for physical skills, to review their medical history, and to perform a physical examination. The athletes receive an orthopedic grade on their ability to participate in the NFL. The purpose of this study was to test the hypothesis that this orthopedic rating at the combine predicts the percent of athletes who play in the NFL and the length of their careers.